PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 166 PEKANBARU - Rasmi, Widya; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the facts found in the class IV SDN 166 Pekanbaru, which shows the results of learning mathematics is still relatively low. Formulation of the problem in this research is: "Is the Application of Cooperative Learning Model Make A Match can improve learning outcomes Mathematics SDN 166 Pekanbaru?". The purpose of this study are: to improve learning outcomes mathematics SDN 166 Pekanbaru through the implementation of cooperative learning model of Make A Match. The hypothesis of this study is that if implemented cooperative learning model of Make A Match it can improve learning outcomes mathematics SDN 166 Pekanbaru. The study was conducted in SDN 166 Pekanbaru in April 2016. This research is a classroom action research (PTK) with two cycles. The subjects were students of class IV SDN 166 Pekanbaru 2014/2015 academic year consisting of 30 students with 15 female students and 15 male students - men. Based on the results of the teacher activity sheet seen rising every meeting. The first meeting in the first cycle percentage (61.11%) with enough categories, the second meeting of the first cycle percentage (75%) with enough category. While on the second cycle, the first meeting with the teacher activity percentage (80.55%) both categories and the second meeting of the activities of teachers percentage (86.11%) in both categories. While the activities of students at the first meeting of the first cycle percentage (58.33%) with enough categories, the second meeting of the first cycle percentage (66.66%) with enough category. While on the second cycle, the first meeting with the student activity percentage (77.77%) both categories and the second meeting of the percentage of student activity (86.11%) in both categories. The results of study in the first cycle increased to 73.83 so has increased by 4.16 points (5.97%) from the base score 69.67. In the second cycle learning outcomes of students increased again to 81.5, occurred an increase in returns of 11.83 points (16.98%). Average value on the basis of a score of 69.67, the first UH increased to 73.83 with an increase of 5,97%. At UH II value - average increased again to 81,5 with an increase of 16,98%. So the results of this study in accordance with the hypothesis ofaction.Key words: Cooperative Learning Model Make A Match, learning outcomes